2017
DOI: 10.1111/desc.12642
|View full text |Cite
|
Sign up to set email alerts
|

Learning by observation and learning by doing in Down and Williams syndromes

Abstract: New skills may be learned by active experience (experiential learning or learning by doing) or by observation of others’ experience (learning by observation). In general, learning by observation reduces the time and the attempts needed to learn complex actions and behaviors. The present research aimed to compare learning by observation and learning by doing in two clinical populations with different etiology of intellectual disability (ID), as individuals with Down syndrome (DS) and individuals with Williams s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Interestingly, the authors found that different genetic profile, brain morphology, and functionality entailed specific profiles of learning in the different ID syndromes. In contrast to subjects with Down syndrome, who benefited from learning by doing, individuals with Williams syndrome benefited from observational training, while they were severely impaired in learning by doing [53].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, the authors found that different genetic profile, brain morphology, and functionality entailed specific profiles of learning in the different ID syndromes. In contrast to subjects with Down syndrome, who benefited from learning by doing, individuals with Williams syndrome benefited from observational training, while they were severely impaired in learning by doing [53].…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have investigated the impact of action observation (AO) on learning procedural skills in ID subjects with genetic etiology [52][53][54]. Interestingly, the authors found that different genetic profile, brain morphology, and functionality entailed specific profiles of learning in the different ID syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, findings from this study may not translate directly to a clinical population of wheelchair users. However, individuals with physical as well as cognitive disabilities also learn skilled movements through motor learning principles [ 64 66 ]. Further studies may examine the effects of propulsion training with VR and AF about propulsion biomechanics on clinical populations such as those who have recently suffered traumatic spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, ndings from this study may not translate directly to a clinical population of wheelchair users. However, individuals with physical as well as cognitive disabilities also learn skilled movements through motor learning principles [64][65][66]. Further studies may examine the effects of propulsion training with VR and AF about propulsion biomechanics on clinical populations such as those who have recently suffered traumatic SCI.…”
Section: Study Limitationsmentioning
confidence: 99%